Implementation of Problem-Solving Oriented RADEC Learning Model in Colloidal Material for the Emergence of Creative Thinking Skills of High School Students - Khaerunnisah, Ida; Sopandi, Wahyu; Wahyu, Wawan (FKIP - Universitas Riau, 2023)
Creative thinking skills are part of Higher Order Thinking Skills (HOTS) that aid students in problem-solving. Teachers have a responsibility to cultivate these skills by employing suitable learning models. The RADEC (Read-Answer-Discuss-Explain-Create) learning model offers an alternative approach for teachers to enhance student competencies. This study aimed to investigate the impact of a problem-solving-oriented RADEC approach through the colloidal topic on students' creative thinking skills. The research was conducted at a private high school in Cianjur Regency and involved 28 students from class XI. The pre-experimental method employed a one-group pre-test and post-test design. The findings revealed that this learning model effectively nurtured students' creative thinking skills. Students demonstrated significant improvements in various aspects of creative thinking, with percentages as follows: fluency (78.88%), flexibility (71.62%), elaboration (68.33%), originality (70.83%), and metaphorical thinking (61.11%). The pre-test and post-test scores indicated an increase in students' creative thinking skills, with an n-gain value of 0.5936, categorized as moderate. In summary, the problem-solving-oriented RADEC learning model proved effective in enhancing students' creative thinking skills in the context of colloidal material. This research has implications for teachers, urging them to consider implementing the RADEC model to foster the development of student's creative thinking abilities.